Population-based rates of revision of primary total hip arthroplasty: a systematic review. - Kelly L Corbett; Elena Losina; Akosua A Nti; Julian J Z Prokopetz; Jeffrey N Katz (PLoS ONE)
Background Most research on failure leading to revision total hip arthroplasty (THA) is reported from single centers. We searched PubMed between January 2000 and August 2010 to identify population- or community-based studies evaluating ten-year revision risks. We report ten-year revision risk using the Kaplan-Meier method, stratifying by age and fixation technique. Results Thirteen papers met the inclusion criteria. Cemented prostheses had Kaplan-Meier estimates of revision-free implant survival of ten years ranging from 88% to 95%; uncemented prostheses had Kaplan-Meier estimates from 80% to 85%. Estimates ranged from 72% to 86% in patients less than 60 years old and from 90 to 96% in older patients. Conclusion Data reported from national registries suggest revision risks of 5 to 20% ten years following primary THA. Revision risks are lower in older THA recipients. Uncemented implants may have higher ten-year rates of revision, regardless of age.